The Relationship Between Disaster Self-Awareness and Junior High School Students' Disaster Preparedness for Mount Merapi Eruption - Anggik Sapuntala; Siti Azizah Susilawati; Siti Hadiyati Nur Hafida; Mohd Hairy Ibrahim (JAMBURA GEO EDUCATION JOURNAL, 2025)
Indonesia's geography poses a threat to society due to its volcanic activity. Disaster self-awareness and disaster preparedness are considered to influence students' actions in dealing with eruptions, both before, during, and after a disaster occurs. Disaster self-awareness enables individuals to take appropriate actions when faced with a disaster, while preparedness involves a series of activities to anticipate disasters. By choosing SMP Negeri 2 Kemalang as the research site, which is close to Mount Merapi, it is hoped that this study can provide a better understanding of how disaster self-awareness can influence students' preparedness in dealing with eruptions. The purpose of the study was to determine the level of disaster self-awareness and preparedness of students at SMP Negeri 2 Kemalang in dealing with the eruption of Mount Merapi, and to determine the relationship between the two variables. The method used in this study is quantitative descriptive with a contingency coefficient correlation design. The results showed that the level of disaster self-awareness of students was 67.50% in the preparedness category. The preparedness variable obtained a percentage score of 77.06%, which is included in the high category. The relationship between the two variables is included in the weak correlation category with a value of 0.298. In an effort to improve students' preparedness for volcanic eruption disasters, schools need to integrate disaster education into the curriculum in a comprehensive and sustainable manner. Further research is needed to evaluate the effectiveness of disaster education programs and to identify other factors that influence optimal student preparedness.